Evaluation of the Financial Performance of the Organization - oglu, Nizomiddinov Jahonmirzo Zukhriddin (European Journal of Life Safety and Stability (2660-9630), 2022)
In market conditions, the company independently plans its own activities and determines development prospects, taking into account the demand for products and based on the need to ensure industrial and social development. Income was a self-planned indicator, among others. Its value is formed under the influence of a large number of different factors and reflects almost all aspects of the enterprise. For this reason, profit can be viewed from the position of a managed object, which can be subjected to planning and forecasting, accounting and analysis, regulation and control.